Fertility Level Waters Based On Abundance Plankton, Nutrients And Water Quality In The Water Merauke Sea Papua Province - Nurjaya, Wayan (Universitas Bengkulu, 2023)
The abundance of plankton holds very important role in determine fertility waters as primary producers in water. The abundance of plankton in a waters generally related with content nutrients that are in waters that. Study this aim for analyze level fertility waters sea merauke based on abundance of plankton and conditions physique chemistry in the water Merauke Sea. Example water is drawn at 25 station with use water sample. Results show abundance plankton in the water Merauke Sea belongs to high. Abundance phytoplankton varied range between 4,047,547 – 1,053,078 ind /m 3 / station. Dominating group is Bacilliophyceae, index diversity (H ') low <1, uniformity almost 0, index dominant low, while zooplankton is also classified as tall with weakness range between 5,500 – 460,281 ind /m3/ station. Condition physical and chemical seawater as temperature including homogeneous that is between 25.95 0 – 27.58 0 C, brightness low 0 – 2 m, turbidity high 2.89 – 730 NTU, pH including homogeneous between 7.06 – 8.11, very high DO between 8.00 – 9.55 mg/L. while nutrients are phosphate enough high.